Strategi dan Ajaran tokoh Syekh Siti Jenar dalam Menyebarkan Agama Islam di Kabupaten Bojonegoro - Salwa Dwi Nur Mukharomah (Tanjak: Sejarah dan Peradaban Islam, 2024)
This article discusses the strategies and teachings of Syekh Siti Jenar. Syekh Siti Jenar is known as one of the figures spreading Islam in Java, especially in the Bojonegoro region in the 15th century. This study examines the strategies and teachings used by Sheikh Siti Jenar in preaching Islam among the people of Bojonegoro. Through a historical approach and analysis of primary and secondary sources, it was found that Sheikh Siti Jenar applied an accommodating method of spreading Islam to local culture. He taught Sufism or Islamic mysticism using language and symbols close to the local community. The strategy of spreading Islam applied by Sheikh Siti Jenar is among others through the teaching of Sufism or Islamic mysticism. He taught the concept of oneness with God (manunggaling kawulo Gusti) which emphasized the union of oneself with the Creator. This teaching is conveyed with language and symbols that are close to the local community, making it easier to accept. In addition, Syekh Siti Jenar also uses cultural arts approaches such as puppet performances and cgamcelanc as da'wah media. He incorporated elements of Islamic teachings into the local culture to attract more people to learn Islam. Although his teachings are considered controversial and considered deviant by some scholars, Sheikh Siti Jenar's approach can facilitate the spread of Islam in the midst of Bojonegoro society which is still thick with local beliefs. However, his contribution in spreading Islam in Bojonegoro and its surroundings should be appreciated as one of the milestones in the history of spreading Islam in the archipelago. This research contributed to enriching the historical treasures of the spread of Islam in the archipelago, especially in the Bojonegoro region at that time